Coronavirus vaccines (COVID-19; SARS-COV-2) in Brazil: an overview (Research, Society and Development, 2021)
The present study aimed at the importance of vaccination against Coronavirus (COVID-19; SARS-COV-2) in Brazil, seeking to describe its effectiveness and the importance of raising awareness of immunization. This is a bibliographic review of the integrative literature review (RIL) type, which presents a qualitative approach. To carry out this study, the following databases were consulted: Medical Literature Analysis and Retrieval System Online (MEDLINE), Scholar Google, Latin American and Caribbean Health Sciences Literature (LILACS), Scientific Electronic Library Online (SCIELO), Repositories and Academic Google. The Descriptors in Health Sciences (DeCS) were used in an associated way: “COVID-19”, “vaccine”, “Brazil”, “Immunization” and “Coronavirus”. Inclusion criteria were: articles available in full, available in Portuguese and English and published between 2019 and 2021. After applying the inclusion criteria, 18 studies remained. Throughout history, it has been observed that programmed and organized vaccination practices prevent millions of deaths and control the evolution of various diseases. In Brazil, vaccination coverage began with two priority groups: health professionals, for being on the front line, and the elderly population, for the higher risk of death from COVID-19, which increases with age, especially among patients with chronic diseases.